2017
DOI: 10.2147/ijwh.s136989
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical paradigm and interpretation of female pelvic floor conditions before a treatment

Abstract: BackgroundFurther progress in restoring a woman’s health may be possible if a patient with a damaged pelvic floor could undergo medical imaging and biomechanical diagnostic tests. The results of such tests could contribute to the analysis of multiple treatment options and suggest the optimal one for that patient.AimTo develop a new approach for the biomechanical characterization of vaginal conditions, muscles, and connective tissues in the female pelvic floor.MethodsVaginal tactile imaging (VTI) allows biomech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…Table 2 lists 52 biomechanical parameters being calculated for every 96 participating subject based on VTI data recorded in tests 1 – 8. Anatomical assignment of the targeting/contributing pelvic structures into the specified parameters is based on already published data [8] [13] [14] [15] [16] [17].…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 lists 52 biomechanical parameters being calculated for every 96 participating subject based on VTI data recorded in tests 1 – 8. Anatomical assignment of the targeting/contributing pelvic structures into the specified parameters is based on already published data [8] [13] [14] [15] [16] [17].…”
Section: Methodsmentioning
confidence: 99%
“…Comparative Test 2 (probe elevation) results for patients with normal pelvic support (no POP) and with stage II POP are presented in Figure 3. Tissue deformation (up to 45 mm) in posterior compartment (see Figure 3(C)) allows acquisition of pressure feedback patterns versus the probe angle to quantify the pelvic floor support at Levels I-III, as defined by DeLancey [19], because the deeper support structures contribute to the pressure patterns on the vaginal wall at such deformations [10]. The tactile ultrasound image fusion (see Figure 4(A) and Figure 4(B)) provides anatomical identification of the levels of support.…”
Section: Resultsmentioning
confidence: 99%
“…A representative study reported a POP surgical failure rate of 61.5% for uterosacral ligament suspension and 70.3% for sacrospinous ligament fixation groups [9]. Substantial improvement is possible if patients with the diseased pelvic floor conditions undergo imaging and biomechanical diagnostic tests, the results of which could be fed into a patient-specific optimal treatment [10] [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biomechanical mapping of a response to applied pressure or load within the pelvic floor opens new possibilities in biomechanical assessment and monitoring of pelvic floor conditions. An innovative approach, vaginal tactile imaging, allows biomechanical mapping of the female pelvic floor including assessment of tissue elasticity, pelvic support and pelvic muscle functions in high definition [13]. This case report on a patient with POP demonstrates preoperative tactile imaging, functional tactile imaging and brings an example of the biomechanical parameters (vaginal tissue elasticity, support structures and functions) of the pelvic floor.…”
Section: Introductionmentioning
confidence: 99%